Analysis of Learning Style and Motivation of Class X High School Students in Phase E in Science-Chemistry Subjects - Musyarofah; Ariyatun (Formosa Journal of Multidisciplinary Research, 2022)
This study aims to describe the learning style and motivation of students in class X Phase E in the Science-Chemistry subject. The research was conducted in an odd semester of the 2022/2023 school year at SMA Negeri 2 Ungaran. The method used in this research is descriptive qualitative method. The research sample was class X students, totaling 317 people. Samples were taken by purposive sampling. Data collection techniques were obtained using a questionnaire. Data was collected and analyzed using descriptive analysis. The results showed that (1) the learning style of students in chemistry learning at SMA Negeri 2 Ungaran which was dominantly practiced by students was visual learning style, (2) the factors that influenced the tendency of students' learning styles were internal and external factors, and (2) factors that influence learning motivation are internal factors in the form of physical and psychological, while external factors are in the form of non-social and social.